Chemistry principles in the laboratory - Slowinski, Emil J (Thomson/Wadsworth, 2005)
CHEMICAL PRINCIPLES IN THE LABORATORY, eighth Edition continues to build on its strengths by clearly presenting the basic principles of chemistry. The lab manual continues to maintain the high quality, time-tested experiments and techniques which have become hallmark features throughout the life of this title.